Research of antifungal effects on some essential oils with tube dilution - Sasmazer, Rukiye Colak; Korukluoglu, Mihriban (Semina: Ciências Agrárias, 2021)
The aim of study to investigate inhibition effects of cinnamic acid (volatile compound of cinnamon), limonene (essential oil of lemon) and eugenol (essential oil of clove, cinnamon) on Metschnikowia fructicola, Candida oleophila, Schisosaccharomyces pombe, Saccharomyces uvarum and Kloeckera apiculata. In this study, tube dilution method was used. Among eugenol, limonene and cinnamic acid, it was found that cinnamic acid has the most inhibition effect with low concentrations (%2.8, %3.84, %4.36, %5,4) at tube dilution methods. Also it was found that test yeast have different resistance against test materials.